Mitigation of efflorescence of wallboard by means of bio-mineralization - Xue, Bin; Qian, Chunxiang (Frontiers in Microbiology, 2015)
Cement-based material is one of the most versatile and largest amount of building materials which can not only be used in load-bearing structure but also decoration materials, like brick, wallboard and tile. However, white calcium carbonate always deposit on the surface of wallboard. This phenomenon generally is called efflorescence, which is not damaging of wallboard, but has aesthetic impact. In this research, Bacillus mucilaginosus was pre-added to the cement matrix to reduce the efflorescence of wallboard. Image processing with software ImageJ, thermogravimetric analysis and permeability test were used to characterize the degree of efflorescence of wallboard. The results showed that the bacterium can capture atmospheric CO2 by carbonic anhydrase and then the CO2 react with Ca(OH)2 produced by cement hydration inside the wallboard. This process can not only reduce the content of Ca(OH)2 but also improve the compactness of wallboard. In addition, the efficiency of resistance to the efflorescence can be achieved when the content of microbial is 4% of cementitious material and the area proportion of surface efflorescence reduced from 32±3% to 5±1%. At the same time, compressive and flexural strength were the highest performance by means of universal testing machine test. The surface of wallboard was the most compact by SEM analysis. The observed efflorescence reduction was indeed due to the effect of bio-mineralization. This promising method is cheap, convenient and environment friendly. It can be massively applied in engineering practice and other fields.